2006
DOI: 10.1073/pnas.0605478103
|View full text |Cite
|
Sign up to set email alerts
|

Cationic amino acid transporter 2 regulates inflammatory homeostasis in the lung

Abstract: Arginine is an amino acid that serves as a substrate for nitric oxide synthase and arginase. As such, arginine has the potential to influence diverse fundamental processes in the lung. Here we report that the arginine transport protein, cationic amino acid transporter (CAT)2, has a critical role in regulating lung inflammatory responses. Analysis of CAT2-deficient mice revealed spontaneous inflammation in the lung. Marked eosinophilia, associated with up-regulation of eotaxin-1, was present in the bronchoalveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…The level of systemic sensitization, as measured by OVA-specific IgG1, was comparable between wild type and CAT2-deficient mice (n = 4 experiments, data not shown). Saline-challenged CAT2-deficient mice had baseline inflammation (primarily neutrophilia) as we have previously reported [8]. In summary, our data demonstrate appropriate inflammatory responses in the lung in response to allergic stimuli.…”
Section: Resultssupporting
confidence: 83%
“…The level of systemic sensitization, as measured by OVA-specific IgG1, was comparable between wild type and CAT2-deficient mice (n = 4 experiments, data not shown). Saline-challenged CAT2-deficient mice had baseline inflammation (primarily neutrophilia) as we have previously reported [8]. In summary, our data demonstrate appropriate inflammatory responses in the lung in response to allergic stimuli.…”
Section: Resultssupporting
confidence: 83%
“…ARG2 is located in the mitochondria, and its higher expression and production of ornithine in asthma may CAT2-deficient mice have spontaneous eosinophilic lung inflammation (18,35). However, expression of CAT2 and CAT3 was similar in bronchial epithelial cells from asthma and control, while CAT1 was undetectable in all samples (n ≥ 3) (data not shown).…”
Section: Resultsmentioning
confidence: 83%
“…Mice harboring mutations of the cationic amino acid transporter-2 (CAT2), which is essential for myeloid cell production of significant amounts of nitric oxide via iNOS, or for significant throughput through the ArgI pathway (45, 46), develop spontaneous lung inflammation at 3 weeks of age (47). One group has reported that global iNOS deficiency results in increased T cell activity (48); also of note are reports that wild type mice show an IFNγ-dependent resistance to autoimmunity, whereas iNOS null mice remain susceptible (49, 50).…”
Section: Discussionmentioning
confidence: 99%